2014
DOI: 10.1063/1.4862751
|View full text |Cite
|
Sign up to set email alerts
|

Scaling behaviors for resistive memory switching in NiO nanowire devices

Abstract: We investigated scaling behaviors for NiO nanowire array devices with different nanowire diameters. Plots of the reset current and the third harmonic generation signal as a function of the on-state resistance (R0) show scaling behaviors for all devices, such as NiO film devices. However, the scaling exponents of NiO nanowire devices were different from those of NiO film devices, and hence the fractal dimension estimated from the scaling exponent was smaller for the NiO nanowire devices than for the NiO film de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…These values are comparable with that of La 2 Mo 2 O 9 , NiO, Nb 2 O 5 , and HfO 2 -based RRAM devices. [36,41,42] The observed scaling law is consistent with the CFs (thermo-chemical) model. The large local current is constricted in the CFs of LRS and the consequent Joule heating increases with increasing the current during the voltage sweep process.…”
supporting
confidence: 80%
“…These values are comparable with that of La 2 Mo 2 O 9 , NiO, Nb 2 O 5 , and HfO 2 -based RRAM devices. [36,41,42] The observed scaling law is consistent with the CFs (thermo-chemical) model. The large local current is constricted in the CFs of LRS and the consequent Joule heating increases with increasing the current during the voltage sweep process.…”
supporting
confidence: 80%
“…This has also been observed in NiO nanowire systems with unipolar switching. 316 Kim et al fabricated NiO nanowires with diameters of 200, 80, and 30 nm, as shown in Fig. 30(a), and measured the scaling exponents from the I reset -R 0 and B 3f -R o plots.…”
Section: Scaling Behaviors Of Physical Propertiesmentioning
confidence: 99%
“…In contrast, the effective dimension should increase with an increase in diameter. As mentioned earlier, Kim et al 316 performed scaling experiments using nanowires with various diameters. The data in the fourth, fifth, and sixth rows of Table III come from nanowires with 200, 80, and 30 nm diameters, respectively.…”
Section: Scaling Theory Based On Fractal Structurementioning
confidence: 99%
“…ReRAM devices are generally composed of a metal–insulator–metal layer structure, predominantly in the form of thin films, deposited from the gas phase. As an alternative to this top–down approach, different bottom–up approaches resulting in nanostructures, like nanowires or nanoparticles (NPs), have been proposed in the literature and well‐defined individual structures, e.g., single cobalt oxide, tin dioxide, and nickel oxide nanowires, showing RS behavior have been described . Recently, BS and CS were shown in ZnO/TiO 2 and ZnO/TiO 2 /ZnO nanowire heterostructures .…”
Section: Introductionmentioning
confidence: 99%